1994
DOI: 10.2190/bmt6-wpjy-fxar-vu06
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Psychosocial Factors on Indian Children's Attitudes toward Computers

Abstract: The purpose of this study was to examine the effects of such psychosocial factors as computer experience, computer usage, future plans regarding computers, and various types of anxiety on children's attitudes toward computers. Subjects consisted of 120 males and 159 females in grades six ( N = 120) and seven ( N = 159), who were enrolled in two single-sex, private, residential schools in Dehru Dun, India. The Bath County Computer Attitudes Survey was used to measure attitudes toward computers. The Spielberger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Other research studies report similar findings demonstrating that computer experience-both the type as well as the amount-is the most significant factor affecting students' attitudes toward computers [30,[40][41][42][43][44], and is also associated with lower levels of computer anxiety [45]. These findings suggest that sufficient opportunity to gain experience with computers leads to positive attitudes toward them and to a reduction in anxiety related to present or future use of computers.…”
Section: Computer Experiencementioning
confidence: 56%
See 2 more Smart Citations
“…Other research studies report similar findings demonstrating that computer experience-both the type as well as the amount-is the most significant factor affecting students' attitudes toward computers [30,[40][41][42][43][44], and is also associated with lower levels of computer anxiety [45]. These findings suggest that sufficient opportunity to gain experience with computers leads to positive attitudes toward them and to a reduction in anxiety related to present or future use of computers.…”
Section: Computer Experiencementioning
confidence: 56%
“…Previous studies show that boys have greater access to, and make more use of computers at home [30,39,43,[46][47][48]. Although in some studies such differences were found to be relatively small, none of them showed girls to have greater access to home computers.…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…Four national studies have reported on the use of computers by non-American students. In a study of Indian children enrolled in two private residential schools, more than 30% of the children reported never using a computer or using a computer a little at school (Miller & Varma, 1994). Israeli children in Tel Aviv in Grades 8 to 10 (where computers had not yet been introduced at school) were asked if they knew how to use a computer; 72% of the female students did not know how, versus 46% of the males (Levin & Gordon, 1989).…”
Section: Computer Familiaritymentioning
confidence: 99%
“…First among them is the discussion of factors that predict students' attitudes to e-learning. Research has established that factors such as age, gender, personality, and previous computer experience are important in shaping students' attitudes toward e-learning (Miller & Varma, 1994;Taylor & Todd, 1995;Sanchez et al, 2006). Thus, users who are young, male, have a higher risk tolerance, and have more experience with computers are more inclined to have positive views of e-learning than users who are not.…”
Section: What Themes Have Attracted Research On E-learning?mentioning
confidence: 99%